Fungsi Dewan Perwakilan Rakyat Daerah Kota Makassar pada Pembentukan Peraturan Daerah Responsif - Ismail Ismail; Andi Pangerang Moenta; Zulkifli Aspan (SASI, 2021)
This research aims to identify and analyze the implementation of the function of The Assembly at Makassar City Regional in the formatting of responsive regional regulation. The type of research used is socio-juridical with sociological juridical, statutory and conceptual approach. The results show that the The Assembly at Makassar City Regional is still less responsive to formatting regional regulations, because it is not selective in choosing the people's wishes and lacks polite politics in formatting of regional regulations which has the implication of producing less responsive regional regulations, especially regarding the setting of distances in measurement between traditional markets and/or modern markets.